High-Efficiency Si Solar Cell Fabricated by Ion Implantation and Inline Backside Rounding Process. (17th December 2012) - Lee, Chien-Ming; Chang, Sheng-Po; Chang, Shoou-Jinn; Wu, Ching-In
Abstract : We introduce a novel, high-throughput processing method to produce high-efficiency solar cells via a backside rounding process and ion implantation. Ion implantation combined with a backside rounding process is investigated. The ion implantation process substituted for thermal POCl3 diffusion performs better R sheet uniformity (<3%). The U-4100 spectrophotometer shows that wafers with backside rounding process perform higher reflectivity at long wavelengths. Industrial screen printed (SP) Al-BSF on different etching depth groups was analyzed. SEMs show that increasing etch depth improves back surface field (BSF). The I -V measurement revealed that etching depths of 6  μ m ± 0.1  μ m due to having the highest V OC and I SC, it has the best performance. SEMs also show that higher etching depths also produce uniform Al melting and better BSF. This is in agreement with IQE response data at long wavelengths.